Vermiculture technology earthworms, organic wastes, and environmental management - Edwards, C. A. (Clive Arthur), 1925-; Arancon, Norman Q.; Sherman, Rhonda L. (Boca Raton, Fla. : CRC Press, 2011)
"Co-edited by international earthworm expert Clive A. Edwards, Vermiculture Technology: Earthworms, Organic Wastes, and Environmental Management is the first international, comprehensive, and definitive work on how earthworms and microorganisms interact to break down organic wastes on a commercial basis. Many books cover the importance of composting for reducing the amount of organic wastes in landfills. This reference focuses on innovative vermiculture technology that turns organic waste into a value-added environmentally friendly products that can improve soil fertility and productivity on a large scale. Chronicles more than two decades of growth and changes in earthworm composting technology Based on the work of an outstanding international cast of scientists, the book explores the dramatic growth and changes in vermiculture technology since 1988 and assesses advances made in government-funded projects in the United States and United Kingdom. The contributors discuss outdoor and indoor windrows, container systems, wedge systems, and low labor-requirement, fully-automated continuous flow vermicomposting reactor systems that can process more than 1000 tons of organic wastes per reactor per annum. They also highlight the science and biology behind the use and efficacy of vermicomposting, examine its importance to developing countries, and detail the technology of the past, present, and future.Although the development of a range of vermicomposting technologies has been rapid and the spread of vermicomposting dramatic, the scientific literature remains scattered throughout a range of journals, newsletters, and online resources. As a compilation of information designed specifically to have an extended shelf life, this volume chronicles how vermiculture can be brought into full commercial and industrial development and find application in integrated waste management systems"--
"Exploring the dramatic growth and changes in the field of vermicomposting since 1988, this comprehensive review assesses the advancements made in government-funded projects in the U.S. and UK. It discusses outdoor or indoor windows, container systems, wedge systems, and low labor-requirement, fully-automated continuous flow vermicomposting reactor systems that can process more than 1000 tons of organic wastes per reactor. It also highlights the science and biology behind the use and efficacy of vermicomposting and details the technology of the past, present, and future"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Earthworm culture; Earthworms; Electronic books